HUBUNGAN FAKTOR RISIKO DENGAN PROPORSI INFEKSI PEDICULUS HUMANUS CAPITIS PADA SISWA - SISWI SEKOLAH DASAR MUHAMMADIYAH 1 DI KOTA MEDAN - SAUBISSABRI SYARBAINI; HEMMA YULFI (JURNAL ILMIAH KOHESI, 2021)
Pediculosis capitis is a cosmopolitan disease that can be found in all level of society, which is caused by lice infestation.Pediculus humanus var. capitis which belongs to the family Pediculidae is one of the causes of hair and head disorders. Thisdisease needs attention because it often attacks children. Pediculosis is still a health problem that needs attention becausethe number of events is so varied and is supported by various risk factors such as cleanliness of the scalp and hair.Todetermine the relationship of risk factors for head lice infestation among students of Muhammadiyah 1 Primary School in Medan.This is a descriptive analytic study, using cross sectional design. Data was obtained by filling out the questionnaire andundertook physical examination from 232 samples, after which were analyzed using statistical test. Statitiscal test resultsshowed an association between the proportion of pediculosis capitis infections with risk factors including hair length(p = 0.001), hair type (p = 0.001), hair washing frequency (P = 0.001), hair cut frequency (p = 0.001) and use of shampoo(p = 0.024). Hair type is more dominant than pediculosis infection (SE = 7.8%). There is a relationship between risk factorsand the proportion of pediculosis capitis in school children.